Moisture problem in hospital building (focus in ward building, Block 001) / Nazrul Ikwan Ismail - Ismail, Nazrul Ikwan (2016)
Hospital building is commonly not access all area especially in the ward, operation room, pharmacy and main office in the hospital. Hospital University Science Malaysia (HUSM) is a government funded medical institution located in Kubang Kerian, Kelantan. The first time going the hospital for observation, many people or patient in the ward and also certain ward cannot access because the critical ward. Then, second time going to hospital, guard in the ward give the permission for access for observation in the ward. Besides, Health Campus, University Science Malaysia (USM) in Kubang Kerian, Kelantan was established in August 1983 dedicated to the field of medicine and medical partial. Rank 5 kilometers from the center of Kota Baharu. Starting with Hospital University Science Malaysia (USM), the campus has grown after the School of Medical Sciences campus in Kelantan moved to an area of 72.84 hectares. The development will be completed in 1990. The building has 8 floors ward, all made in the ward started from level 1 to level 8. A study was carry out through the collection of information and data from interviews and observation in the ward. The study conducted at one case study only. The objective of this study is to explore the causes and effect problem in hospital building, focus in the ward and the second objective which is to recommend prevention of moisture in hospital building. the finding and analysis about the observation to successful and complete of my dissertation.